Definition and design: aligning language interventions in education - Weideman, Albert (Stellenbosch Papers in Linguistics Plus, 2019)
The management of language diversity and the mastery of language required by educational institutions affect those institutions from early education through to higher education. This paper will deal with three dimensions of how language is managed and developed in education. The first is the design of interventions for educational environments at policy level, as well as for instruction and for language development. The second dimension concerns defining the kind of competence needed to handle the language demands of an academic institution. The interventions can be productive if reference is made throughout to the conditions or design principles that language policies and language courses must meet. The third dimension concerns meeting an important requirement: the alignment of the interventions of language policy, language assessment and language development (and the language instruction that supports the latter). The paper will use a widely used definition of academic literacy to illustrate how this supports the design of language assessments and language courses. It is an additional critical condition for effective intervention design that assessments and language instruction (and development) work together in harmony. Misalignment among them is likely to affect the original intention of the designs negatively. Similarly, if those interventions are not supported by institutional policies, the plan will have little effect. The principle of alignment is an important, but not the only design condition. The paper will therefore conclude with an overview of a comprehensive framework of design principles for language artefacts that may serve to enhance their responsible design.